CONSTRUCTION RIPPLE PHENOMENON AND THE RISE OF ‘GENERIC BUILDINGS’ IN YOGYAKARTA - Mahendarto, Trias (Jurnal Arsitektur Komposisi, 2018)
Abstract: Starting from the past decade, Indonesia is growing rapidly in the construction of infrastructures that are being fully supported by the government in order to reach the goal of becoming one of the leading countries in the future. Such development created the construction ripple phenomenon that was instigated by the private sector to fill the construction voids left by the rapid development of infrastructure, and it pressurizes cities to grow or change in order to coup with the infrastructure advancements. This phenomenon has affected the cities in Indonesia, even those that are not considered as the planned centers of developments, such as Yogyakarta. Yogyakarta is experiencing the effects of the ripple in the form of the rising number of generic buildings that are spreading fast around the city. This will, in turn, dictate the future of Yogyakarta’s ever-evolving Genius Loci. This research will see how much the construction ripple phenomenon has affected the city of Yogyakarta by conducting surveys on the generic buildings that have been built or in the planning stage of construction. A thorough analysis will be then made, also by conducting literature studies, to conclude the ways and steps to try maintaining Yogyakarta’s unique characteristic as a city in the ever-growing pressure of economic modernization that is currently spreading throughout Indonesia. If these steps are being done correctly, then Yogyakarta can become one of the examples of how cities in Indonesia coup with the construction ripple phenomenon without can losing its unique urban characteristics. Keywords: construction ripple phenomenon, Yogyakarta, Generic buildings, Genius LociAbstrak: Semenjak decade terakhir, Indonesia sedang mengalami perkembangan signifikan di bidang pembangunan infrastuktur yang didukung penuh oleh Pemerintah agar dapat mengejar target untuk menjadi salah satu negara maju di masa depan. Perkembangan tersebut memunculkan fenomena ‘construction ripple’, yang didorong oleh sektor swasta untuk mengisi kekosongan pembangunan karena pemerintah hanya berkonsentrasi pada pembangunan infrastuktur, dan hal tersebut menekan kota-kota untuk berkembang atau berubah. Fenomena ini telah terjadi di berbagai kota di Indonesia, bahkan di kota yang tidak menjadi pusat perkembangan infrastuktur, seperti kota Yogyakarta. Yogyakarta sedang mengalami efek dari fenomena ini dalam bentuk munculnya bangunan generik yang tersebar luas di seluruh kota. Perkembangan ini akan mempengaruhi masa depan Genius Loci kota Yogyakarta, yang terus berevolusi. Penelitian ini melihat sejauh mana bangunan generik mempengaruhi kota Yogyakarta, melalui survey bangunan generik yang terbangun atau sedang dalam proses pembangunan. Analisis mendalam dilakukan, dengan disertai studi literatur, untuk melihat cara menjaga keunikan kota Yogyakarta terhadap tekanan pembangunan yang terus terjadi. Diharapkan kota Yogyakarta menjadi contoh kota-kota di Indonesia menerima efek fenomena ‘construction ripple’ tanpa kehilangan kekhasan.Kata kunci: construction ripple phenomenon, Yogyakarta, bangunan generik, Genius Loci